A systematic assessment of adverse event reporting in selected state hospitals in Sri Lanka - Mallawarachchi, S.M.N.S.M.; Dharmarathna, G.S.K. (Journal of Surgery and Medicine, 2022)
Background/Aim: Patient safety is an integral component of health care. Adverse event reporting plays a key role in ensuring patients’ safety. The Sri Lankan Ministry of Health has introduced guidelines and a system of adverse event reporting. Here we assess the pattern of adverse event reporting in selected 46-line ministry hospitals. Methods: The adverse events reported in the year 2019 were analyzed. The frequency of reporting of each event was assessed. The issues in relation to adverse event reporting and root causes were assessed through focus group discussions with selected hospital administrators. Results: Most reported events were “patient falls”, contributing to 30.46% of the total. Availability of guidelines, well-established quality management units, and a non-punitive non-fault-finding approach to adverse event reporting and analysis process were identified as strengths of the system. But lengthy paper-based documentation process was recognized as a major weakness. Conclusion: Although the state health sector of Sri Lanka has an established system of adverse event reporting, it is mostly limited to non-clinical events such as falls. Fear of blame and shame among staff and the lengthy paper-based reporting system have negatively affected the process.